2011
DOI: 10.1080/09603107.2010.533998
|View full text |Cite
|
Sign up to set email alerts
|

The smooth transition GARCH model: application to international stock indexes

Abstract: The aim of this article is to study the dynamics of four international stock indexes, by developing a model that introduces asymmetry and nonlinearity on the conditional variance. The Smooth Transition Generalized Autoregressive Conditional Heteroscedastic (STGARCH) model is considered, where the possibility of intermediate regimes is modelled with the introduction of a smooth transition mechanism in a Generalized Autoregressive Conditional Heteroscedastic (GARCH) specification. The transition function is eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A series of researches hire the smooth transition concept and apply to GARCH specification (e.g. Hagerud, 1997;Gonza´lez-Rivera, 1998;Anderson et al 1999;Lundbergh and Tera¨svirta, 2002;Lanne and Saikkonen, 2005;Liau and Yang, 2008;Jawadi et al, 2010;Khemiri, 2011).…”
Section: The St-garch Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of researches hire the smooth transition concept and apply to GARCH specification (e.g. Hagerud, 1997;Gonza´lez-Rivera, 1998;Anderson et al 1999;Lundbergh and Tera¨svirta, 2002;Lanne and Saikkonen, 2005;Liau and Yang, 2008;Jawadi et al, 2010;Khemiri, 2011).…”
Section: The St-garch Modelmentioning
confidence: 99%
“…They apply this method on the mean equation. Hagerud (1997), Gonza´lez-Rivera (1998), Anderson et al (1999), Lee and Degennaro (2000), Lundbergh and Tera¨svirta (2002), Lanne and Saikkonen (2005), Liau and Yang (2008), Jawadi et al (2010) and Khemiri (2011) apply the smooth transition method on the volatility equation further. We employ a more flexible smooth transition Generalized Autoregressive Conditional Heteroscedastic (GARCH) model proposed by Lundbergh and Tera¨svirta (2002).…”
Section: Introductionmentioning
confidence: 98%
“…Large number of researches (Karolyi, 1995;Hong, 2001;Koopman et al, 2005;Hammoudeh and Li, 2008;Khemiri, 2011;Bonilla and Sepulveda, 2011;Fiszeder and Orzeszko, 2012;Salma, 2015;Mittal and Kumar, 2016;Demirer, Gupta and Wong, 2019) adopted non-linear ARCH/GARCH family models (Engle, 1982;Bollerslev, 1986) for probing precariousness of different types of time series data. The literature further state that predominance of the research studies in Asia have implemented vector autoregression (VAR) framework, Cointegration and Granger causality test only (Joshi, 2011;Tuan et al, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Srinivasan & Ibrahim (2010) forecasted Stock Market Volatility of BSE-30 Index with the help of GARCH models based on the daily data and results led to the conclusion that symmetric GARCH (1,1) model performed better in forecasting the conditional variance of the Sensex daily returns compared to EGARCH (1,1) and TGARCH (1,1) models. Khemiri (2011) analysed the dynamics of four international stock indices by applying Smooth Transition GARCH (STGARCH) model. The results showed that in Logistic Smooth Transition GARCH (LSTGARCH) model return shock's sign on asymmetric conditional volatility is stressed and Exponential Smooth Transition GARCH (ESTGARCH) model highlighted the price shock's magnitude effect on the subsequent volatility.…”
Section: Literature Reviewmentioning
confidence: 99%